3D printed silicone spinal cord implant with sub-millimeter feature size (Transactions on Additive Manufacturing Meets Medicine, 2022)
Spinal cord injury (SCI) can lead to the dysfunction of nerve fibers by hemi- or complete transection, resulting in permanent paraplegia. In recent years, a number of therapies have been developed to treat spinal cord injury. A mechanical microconnector system (mMS) that supports the regeneration of nerve fibers after SCI through a combination of different therapies was designed in previous works. For this implantable mMS with minimum feature size of a few hundreds of micrometers, it is essential to provide fast, flexible, three-dimensional fabrication. This paper describes a new fabrication method of the mMS made of silicone using additive manufacturing based on a commercially available material jetting printer. The application of this technology advances the fabrication and adaptability of mMS in terms of higher elasticity of the implant using silicone and additionally with respect to high customizability and rapid prototyping using additive manufacturing. We show the successful adaption and realization of a silicone-based mMS dimensioned for a human model with structure sizes down to 300 um. We elaborate the advantages and disadvantages of additive, silicone-based 3D printing for this application in comparison to molding-based and subtractive 3D printing methods, thus demonstrating the relevance of this technology for medical application.
Keywords: Spinal Cord Injury; 3D printed Implant; Silicone Printing; Small Scale 3D Printing